Analisis Kinerja Keuangan Desa Ditinjau dari Pendapatan dan Belanja Desa pada Desa Reroroja Kecamatan Magepanda Kabupaten Sikka - Valentin Romualda Gaudiosa Bella Adur; Pipiet Niken Aurelia; Paulus Libu Lamawitak (Journal of Management and Bussines (JOMB), 2023)
This research aims to determine the financial performance of Reroroja Village, Magepanda District, Sikka Regency. The method used in this research is a quantitative descriptive research method. The data used is the Realization Report of the Village Revenue and Expenditure Budget (APBdes) of Reroroja Village for the 2017-2021 Fiscal Year. The results of the research show that 1) the Reroroja Village Revenue Effectiveness Ratio from the 2017 Fiscal Year to the 2021 Fiscal Year is very effective with an average effectiveness of 100.01%. These results indicate that the performance of the Reroroja village government is very good; 2) The Efficiency Ratio of Village Expenditures compared to Reroroja Village Revenue from the 2017 Fiscal Year to the 2021 Fiscal Year is less efficient with an average efficiency of 99.59%, meaning that the financial performance of the Reroroja village government is not good. 3) The Income Growth Ratio of Reroroja village is very low with a growth ratio of 11.08%; Likewise, the average growth in Reroroja village expenditure is very low with a growth ratio of 10.33%. Keywords: Effectiveness Ratio, Efficiency Ratio, Growth Ratio